Aplikasi Pembelajaran Kesehatan bagi Masyarakat pada Puskesmas Kecamatan Kemayoran Berbasis Web dengan Moodle - Zakiyah, Dini; Nurin, Resza Manzilina (Teknik Informatika Universitas Pamulang, 2020)
District Health Center of Kemayoran is one of the medical institutions that provide health services 24 hours to the community, especially those residing in the district of Kemayoran. The center often conducts activities such as socialization or counseling to increase public knowledge regarding the importance of maintaining health. Puskesmas is not enough to provide health care only through direct socialization. This is because of the limited time and place to convey health information and not all people follow the socialization because it has other activities that they cannot live. This research aims to produce a health information application that can be learned electronically that can provide learning about health-related symptoms and how to prevent an illness to the community. The research was developed using the waterfall method with Unified Modeling Language (UML) modeling. The result of this research is a health information application that can provide health learning to the community so as to increase the willingness of healthy life independently.